The role of NUPR1 in lymphocyte proliferation and apoptosis - Vujičić, Milica; Vasić, Bobana; Nikolić, Ivana; Saksida, Tamara; Stojanović, Ivana (Archives of Biological Sciences, 2017)
Nuclear protein 1 (NUPR1) is a transcription cofactor that senses stressful conditions and modulates cellular response by promoting or inhibiting apoptosis. NUPR1 is usually highly expressed in tumor cells where it enables them to adapt and resist environmental stress or chemotherapeutic compounds. NUPR1 can be involved in cell proliferation. Data about the involvement of NUPR1 in the proliferation and apoptosis of lymphocytes are scarce. Therefore, in this study we focused on the role of NUPR1 in lymphocyte physiology and found that NUPR1 might be involved in the initiation of their proliferation. Lymphocytes were isolated from the cervical lymph nodes of C57BL/6 mice. NUPR1 expression subsided 24 h after the induction of proliferation by a mitogen. Also, stressful conditions after cell isolation led to increased NUPR1 mRNA and protein expression in vitro that coincided with cell apoptosis. Similarly, apoptosis induction by staurosporine, a broad-range protein kinase inhibitor, led to increased NUPR1 expression. In addition, NUPR1 inhibition by small-interfering RNA prevented the staurosporine-induced apoptosis (judging from decreased caspase activity) in the whole cell population of cervical lymph nodes. However, NUPR1 absence was irrelevant to the induction of apoptosis in CD3+ T lymphocytes, suggesting that NUPR1 is probably a mediator of apoptosis in other immune cell populations within the lymph node, such as B lymphocytes. In conclusion, our results suggest that NUPR1 is important for the initiation of lymphocyte cell division and for the apoptotic process of non-T cells during stressful conditions. https://doi.org/10.2298/ABS160707096V Received: July 7, 2016; Revised: October 7, 2016; Accepted: October 7, 2016; Published online: October 14, 2016 How to cite this article: Vujičić M, Vasić B, Nikolić I, Saksida T, Stojanović I. The role of NUPR1 in lymphocyte proliferation and apoptosis. Arch Biol Sci. 2017;69(2):261-7.